Glucagon: a potential protective factor against peripheral nerve compromise in patients with type 2 diabetes and obesity - Hao Hua; Rui Wang; Yu-xian Xu; Feng Xu; Chun-hua Wang; Li-hua Zhao; Li-hua Wang; Cheng-wei Duan; Jian-bin Su (Diabetology & Metabolic Syndrome)
Abstract Background Increased glucagon levels are now recognized as a pathophysiological adaptation to counteract overnutrition in type 2 diabetes (T2D). This study aimed to elucidate the role of glucagon in peripheral nerve function in patients with T2D with different body mass indices (BMIs). Methods We consecutively enrolled 174 individuals with T2D and obesity (T2D/OB, BMI ≥ 28 kg/m2), and 480 individuals with T2D and nonobesity (T2D/non-OB, BMI < 28 kg/m2), all of whom underwent oral glucose tolerance tests to determine the area under the curve for glucagon (AUCgla). Electromyography was utilized to assess overall composite Z-scores for latency, amplitude, and nerve conduction velocity (NCV) across all peripheral nerves, specifically examining the median, ulnar, common peroneal, posterior tibial, superficial peroneal, and sural nerves. Results In the T2D/OB group, the AUCgla exhibited a significant correlation with the latency, amplitude and NCV of each peripheral nerve, as well as with the overall composite Z-scores for latency (r = –0.283, p < 0.001), amplitude (r = 0.295, p < 0.001), and NCV (r = 0.362, p < 0.001). In contrast, the T2D/non-OB group did not exhibit obvious correlations between the AUCgla and the overall composite Z-scores for latency (r = –0.088, p = 0.056), amplitude (r = 0.054, p = 0.251), and NCV (r = 0.116, p = 0.012). Furthermore, multivariate linear regression analyses indicated that elevated AUCgla was independently associated with a lower overall composite Z-score for latency (β = –0.304, t = –3.391, p = 0.001), as well as higher overall composite Z-scores for amplitude (β = 0.256, t = 2.630, p = 0.010) and NCV (β = 0.286, t = 3.503, p = 0.001), after adjusting for other clinical covariates within the T2D/OB group. Conclusion Increased glucagon levels may be a potential protective factor against peripheral nerve compromise in patients with T2D and obesity.